Analysis of Project Management Methodologies in IT Industry - Krasnokutska Natalia S. (Bìznes Inform, 2020)
The purpose of the article is to study the methodologies of project team management in the field of software development. Analyzing, systematizing and generalizing scientific works of scientists and project management standards, world standards and practices were considered, the analysis of implementation of world standards by project managers in Ukraine was performed. Particular attention is paid to software development methodologies used under the conditions of work distributed project teams because this is the most favorable form of labor organization during a pandemic. The methodologies of project management used for the work of distributed project teams in Ukraine are allocated. It is identified that the most popular methodology in the world and in Ukraine in terms of the use of both the distributed teams and the teams working in one location is the Scrum-methodology of software development. It is substantiated that the methodologies used by project managers in Ukraine for their own projects do not differ from world practices and standards, except for a few methodologies such as Lean and Prince 2, which have not become popular among managers in Ukraine. In addition, the significant difference that is observed is 10% of difference between the frequent use of Kanban methodology in Ukraine and in the world. This difference, as we assume, indicates that in Ukraine there is a higher percentage of projects supported by the distributed project teams rather than are developed from scratch, so the percentage of using the Kanban methodology is higher. Prospects for further research in this direction are to determine the degree of implementation of all the principles of methodologies in the distributed project team in Ukraine and the effectiveness of work of such teams.